2021
DOI: 10.1177/08933189211006390
|View full text |Cite
|
Sign up to set email alerts
|

High Reliability Collaborations: Theorizing Interorganizational Reliability as Constituted through Translation

Abstract: High reliability organizations (HROs) need to collaborate to address risks that transcend organizational boundaries. HRO literature has yet to examine the challenge of creating interorganizational reliability, while collaboration literature can further explore how stakeholder priorities become dominant in collaborations. This study joins these bodies of literature to identify the growing domain of High Reliability Collaborations (HRCs). Drawing from 2 years of ethnographic research within a community emergency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…In fact, reliability is “as much of a product of a relationship as it is a feature of the relationship” (Berthod et al, 2015, p. 26). Relating to each other is an important step in networks that strive for reliability (Rice, 2021). In the case of a global public health crisis, organizations may interrelate through the practices identified here by sharing information about the hazard, comparing their response to other organizations, and ultimately creating meaning together about the successes and failures of their performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, reliability is “as much of a product of a relationship as it is a feature of the relationship” (Berthod et al, 2015, p. 26). Relating to each other is an important step in networks that strive for reliability (Rice, 2021). In the case of a global public health crisis, organizations may interrelate through the practices identified here by sharing information about the hazard, comparing their response to other organizations, and ultimately creating meaning together about the successes and failures of their performance.…”
Section: Discussionmentioning
confidence: 99%
“…This appears to be an incentive for many non-HROs to strive for reliability as well (Weick & Sutcliffe, 2007). This inclusion has created the opportunity to bring to the fore how reliability is created in response to complex and cascading disasters (Clark-Ginsberg et al, 2021) and through interorganizational relationships (Berthod et al, 2017;Rice, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifth, HRT members ( 5) "translate" their reliability values strategically when collaborating with outsider and non-HRT members. Rice's (2021) ethnographic study of HRTs' interorganizational collaborations with external stakeholders revealed the strategic ways members persuade non-HRT outsiders to enact high reliability. Specifically, HRT members tended to engage in substantial informal talk with non-HRT members as a means of translating their high reliability mental schemas and assumptions.…”
Section: Explanation Of Team Member Practices That Enact and Encourag...mentioning
confidence: 99%
“…At this time man does everything more practically, quickly and efficiently. So that tool technology that was previously made manually began to be abandoned in use in society (Rice & Pennington, 2024). One example of an intravenous fluid monitoring device.…”
Section: Introductionmentioning
confidence: 99%